Use of different PCR primers and gastric biopsy tissue from CLO test for the detection of Helicobacter pylori - Sukanya Linpisarn (2018)
Four different DNA loci were assessed for the detection of H. pylori by PCR on gastric biopsy specimens. PCR, with a primer specific 860 bp DNA fragment, was the most sensitive, with a detection limit of 0.02 pg H. pylori DNA, corresponding to approximately 10 organisms. Nested-PCR of the 860-bp DNA fragment was 10-fold more sensitive than single-step PCR. The sensitivity and specificity of the four PCR methods, in comparison to the results obtained from histology and the urease test, are as follows: 80.7% and 76% for the hpaA gene; 100% and 76% for the 16S rRNA gene; 84.6% and 80.0% for the 860-bp DNA fragment; 61.5% and 84.0% for the ureC (glmM) gene, respectively. The sensitivity of nested-PCR for the 860-bp DNA fragment was 100%. This nested-PCR gave positive results for eight specimens which were negative by conventional methods. PCR can be performed on gastric biopsy specimens obtained from the CLO test.